Can 8-weeks of Training Affect Active Drag in Young Swimmers? - Marinho, Daniel (2010)
The aim of this study was to assess the effects of 8-weeks of training on active drag in young swimmers of both genders. Eight girls and twelve boys' belonging to the same swimming team and with regular competitive participation in national and regional events for the previous two seasons participated in this study. Active drag measurements were conducted in two different evaluation moments: at the beginning of the season and after 8 weeks of training (6.0 ± 0.15 training units per week, 21.00 ± 3.23 km per week and 3.50 ± 0.23 km per training unit). The maximal swimming velocity at the distance of 13 m, active drag and drag coefficient were measured on both trials by the method of small perturbations with the help of an additional hydrodynamic body. After 8 weeks of training, mean active drag (drag force and drag coefficient) decreased in girls and boys, although no significant differences were found between the two trials. It seems that 8 weeks of swimming training were not sufficient to allow significant improvements on swimming technique. Key pointsThe velocity perturbation method seems to be a good, simple and reliable approach to assess active drag in young swimmers.Eight weeks of swimming training were not sufficient to allow significant improvements on swimming hydrodynamics.There were no differences between boys and girls concerning active drag. A possible explanation may be related to the similar values of body mass and height in boys and girls found in this study.Specific training sets concerning technique correction and improvement in young swimmers might be a main aim during training planning.